Dental assessment of Stegoceras validum (Ornithischia: Pachycephalosauridae) and Thescelosaurus neglectus (Ornithischia: Thescelosauridae): paleoecological inferences. (February 2022) - Hudgins, Michael Naylor; Currie, Philip J.; Sullivan, Corwin
Abstract: Small herbivorous dinosaurs of the clades Pachycephalosauridae and Thescelosauridae occur in multiple Cretaceous formations in North America, their coexistence likely made possible by differences in feeding style. Fossils of these taxa are generally rare, but isolated pachycephalosaurid and thescelosaurid teeth are common at microfossil sites, and easily confused with one another in field and museum settings. Using qualitative features and a set of 12 measurements, the dentitions of the pachycephalosaurid Stegoceras validum and the thescelosaurid Thescelosaurus neglectus were compared, based on teeth preserved in identified skeletons. S. validum and T. neglectus possess heterodont dentitions, and their teeth differ in size, denticulation, crown symmetry, root and crown cross-sectional shapes, apical geometry, crown ornamentation, and wear facet patterns. Principal components analysis of the measurements shows that T. neglectus premaxillary, maxillary, and dentary crowns are readily morphologically distinguishable from one another, whereas all S. validum crowns cluster close to each other and to dentary crowns of T. neglectus . Linear discriminant analysis shows little overlap between S. validum and T. neglectus . The results indicate strong heterodonty in T. neglectus, whereas S. validum teeth are more uniform. Dental differences between the two species may imply that they differed in feeding function. The teeth of T. neglectus, combined with the narrow rostrum, suggest a selective feeding strategy. By contrast, S. validum has a wide rostrum and may have engaged in indiscriminate bulk-feeding behavior. This analysis of dental differences between S. validum and T. neglectus should facilitate identification of isolated pachycephalosaurid and thescelosaurid teeth from microfossil sites.